Ceiba Pentandra Seed Extract as Green Corrosion Inhibitor for Mild Steel in Citric Acid Media: Electrochemical Investigation - Syarif Hidayatullah; Suteja Suteja (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2026)
In citric acid medium, Ceiba pentandra seed extract an agricultural by product contains abundant heterocyclic and nitrogen-containing compounds that function as efficient and environmentally benign corrosion inhibitors. Compared with conventional synthetic inhibitors, plant-based extracts offer notable advantages, including low toxicity, biodegradability, renewability, and cost-effectiveness. The extract was prepared using the reflux method and tested at concentrations ranging from 1000 to 3000 ppm. The active functional groups were identified by Fourier Transform Infrared Spectroscopy (FTIR), while corrosion inhibition performance was evaluated using Potentiodynamic Polarization (PDP) and Electrochemical Impedance Spectroscopy (EIS). At 3000 ppm, the extract exhibited inhibition efficiencies of 81.42% (PDP) and 74.21% (EIS), attributed to the adsorption of aromatic, heterocyclic, and carbonyl groups onto the metal surface. These findings confirm the potential of Ceiba pentandra seed extract as a sustainable, low-cost, and high-performance green corrosion inhibitor, underscoring its promise as an environmentally safe alternative to conventional hazardous inhibitors.